Housing Instability Following Felony Conviction and Incarceration: Disentangling Being Marked from Being Locked Up - Bryan, Brielle (Journal of quantitative criminology, 2023)
Objectives I examine housing instability among individuals with a felony conviction but no incarceration history relative to formerly incarcerated individuals as a means of separating the effect of felon status from that of incarceration per se—a distinction often neglected in prior research. I consider mechanisms and whether this relationship varies based on gender, race/ethnicity, time since conviction, and type of offense. Methods I use National Longitudinal Survey of Youth 1997 data and restricted comparison group, individual fixed effects, and sibling fixed effects models to examine residential mobility and temporary housing residence during early adulthood. Results I find robust evidence that never-incarcerated individuals with felony convictions experience elevated risk of housing instability and residential mobility, even after adjusting for important mediators like financial resources and relationships. The evidence that incarceration has an additional, independent effect on housing instability is weaker, however, suggesting that the association between incarceration and housing instability found in prior studies may largely be driven by conviction status. Conclusions These findings reveal that conviction, independent of incarceration, introduces instability into the lives of the 12 million Americans who have been convicted of a felony but never imprisoned. Thus, research that attempts to identify an incarceration effect by comparing outcomes to convicted individuals who receive non-custodial sentences may obscure the important independent effect of conviction. Moreover, these findings highlight that the socioeconomic effects of criminal justice contact are broader than incarceration-focused research suggests. Consequently, reform efforts promoting the use of community corrections over incarceration may do less to reduce the harm of criminal justice contact than expected.